Clinical management of supernumerary teeth: A report of two cases - Mittal M; Sultan A (Wolters Kluwer Medknow Publications, 2010)
Supernumerary tooth may closely resemble the teeth of the group to which it belongs, i.e. molars, premolars or anterior teeth, or it may bear little resemblancein size or shape to which it is associated. Many complications can be associated with supernumeraries, like impaction, delayed eruption or ectopic eruption of adjacent teeth, crowding, development of median diastema and eruption into floor of the nasal cavity. This may also cause the formation of follicular cysts with significant bone destruction. Early intervention to remove it is usually required to obtain reasonable alignment and occlusal relationship. This article will present the clinical management of an (i) impacted supernumerary tooth impeding the eruption of maxillary central incisor and (ii) erupted supernumerary tooth with midline diastema.